DETERMINATION OF ENVIRONMENTAL LOAD FACTOR FOR THREE-LEGGED FLARE JACKET OFFSHORE PLATFORM IN THE NORTHERN WATER OF MADURA USING RELIABILITY ANALYSIS METHOD - Revo Refaldiano, Don
The environmental load factor in the ISO 19902 needs to be calibrated in advance, regarding the calibrated value in ISO 19902 are only for Gulf of Mexico, North Sea, and Australia. The objective in this research is to calibrate the environmental load factor that suited the three-legged jacket flare structure in the Northern Water of Madura – one of the oil and gas offshore fields in Indonesia. Variables considered as random variables are wave height, current velocity, yield strength, modulus of elasticity, and correction factor, while for wind velocity is considered as deterministic through the sensitivity analysis. Furthermore, the structure load is modelled as a function of wave height and current velocity for the reliability analysis FORM II. Through the reliability analysis using FORM II, the reliability index for the API RP 2A-WSD design is 2.34. Meanwhile, the reliability index for ISO 19902 design for environmental factors of 1.35, 1.25, 1.22, 1.15, and 1.05 are 2.53, 2.38, 2.34, 2.23, and 2.09. Thus, the environmental load factor that suited ISO 19902 with the target of API RP 2A-WSD design result is 1.22.